Benefits of Prenatal Exercise as Perceived by Pregnant Women Attending Antenatal Clinic in Federal Teaching Hospital Abakaliki (FETHA) - Elom, Nwamaka; Ilo, Cajetan; Ogodo, Juliet (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
This study determines perceived benefits of pre-natal exercise among pregnant women attending antenatal clinic at Federal Teaching Hospital, Abakaliki based on parity and location. Two research questions and two corresponding research hypotheses guided the study. The study adopted survey design, with7200 as the population of the study while the sample was 720 pregnant women attending antenatal clinic at Federal Teaching Hospital Abakaliki. Self-developed structured questionnaire was used as the instrument for data collection. Mean and standard deviation were used to answer the research question while ANOVA and t-test statistic were used to test the hypotheses at 0.05 level of significance. The study found out that pregnant women attending antenatal clinic at Federal Teaching Hospital Abakaliki had positive perception on the benefits of pre-natal exercise based on parity and location and also there were significant differences based on parity and location. The study therefore, recommended that Government, Non–Governmental Organizations (NGO) and health educators should organize workshop, seminar and health talks during the women annual gathering in churches, villages and antenatal visit on the usefulness of prenatal exercise to continue sustaining the positive perception of these women on the benefits of pre-natal exercise.